Strengthening children's religious character through learning to read al-qur'an ummi method in a private home in Probolinggo City - Ulin Nuha, Nazahah; Putri, Wieke Adinda (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2024)
This study aims to strengthen several aspects of religious character in children through the learning method of reading the Ummi Al-Qur'an. The research method used is a qualitative method with a case study approach. Data were collected through interviews, observations, and document analysis of a number of children who participated in learning to read the Qur'an with the Ummi method in private homes. In addition, data were also obtained from parents or guardians of students, teaching teachers, and related literature. The results showed that learning to read the Qur'an with the Ummi method in private homes has a positive influence on strengthening children's religious character in Probolinggo City. This approach not only emphasizes on fluent reading skills, but also on deep understanding and full application of Islamic teaching. This approach has proven effective in overcoming some of the obstacles that arise in the process of learning the Qur'an, such as difficulties in reciting fluently, lack of understanding of religious material, lack of motivation, and lack of knowledge about religious aspects. This research makes a positive contribution to the development of Qur'an learning methods that focus more on strengthening children's religious character in the family environment.